Bogor Botanic Gardens - Ariati, Siti Roosita; Widyatmoko, Didik (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2019)
Bogor Botanic Gardens (BBG) was established in 1817 and is the oldest botanic garden in South East Asia. The garden has long been a centre for scientific research and has been the founding institution of a number of other research centres in Indonesia, particularly in the life sciences. The garden initially covered 47 ha but has expanded over the years and is now 87 ha. It has evolved over its 200-year history from a collection of economically valuable plants to the multi-faceted institute it is today, undertaking activities in plant conservation, research, education, ecotourism and environmental services. In recent years, it has strengthened its role in plant conservation through the establishment of 32 new botanic gardens across Indonesia. These new gardens are managed by local government and universities and supervised by BBG. In its bicentenary year, 2017, BBG organised a number of activities, programmes and celebrations and these are highlighted in thisarticle.